Antimicrobial, Antioxidant, and Anti-Inflammatory Activities of Essential Oils of Selected Aromatic Plants from Tajikistan - Sharopov, Farukh (Foods, 2015)
Antimicrobial, antioxidant, and anti-inflammatory activities of the essential oils of 18 plant species from Tajikistan (Central Asia) were investigated. The essential oil of Origanum tyttanthum showed a strong antibacterial activity with both minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of 312.5 µg/mL for E. coli, 625 µg/mL (MIC) and 1250 µg/mL (MBC) for MRSA (methicillin-resistant Staphylococcus aureus), respectively. The essential oil of Galagania fragrantissima was highly active against MRSA at concentrations as low as 39.1 µg/mL and 78.2 µg/mL for MIC and MBC, respectively. Origanum tyttanthum essential oil showed the highest antioxidant activity with IC(50) values of 0.12 mg/mL for ABTS (2,2′-azino-bis-(3-ethylbenzthiazoline-6-sulfonic acid)) and 0.28 mg/mL for DPPH (2,2-diphenyl-1-picrylhydrazyl). Galagania fragrantissima and Origanum tyttanthum essential oils showed the highest anti-inflammatory activity; IC(50) values of 5-lipoxygenase (5-LOX) inhibition were 7.34 and 14.78 µg/mL, respectively. In conclusion, essential oils of Origanum tyttanthum and Galagania fragrantissima exhibit substantial antimicrobial, antioxidant, and anti-inflammatory activities. They are interesting candidates in phytotherapy.